2008
DOI: 10.1105/tpc.108.058867
|View full text |Cite
|
Sign up to set email alerts
|

Mutation ofArabidopsis BARD1Causes Meristem Defects by Failing to ConfineWUSCHELExpression to the Organizing Center  

Abstract: Stem cell fate in the Arabidopsis thaliana shoot apical meristem (SAM) is controlled by WUSCHEL (WUS) and CLAVATA. Here, we examine BARD1 (for BRCA1-associated RING domain 1), which had previously been implicated in DNA repair functions; we find that it also regulates WUS expression. We observed severe SAM defects in the knockout mutant bard1-3. WUS transcripts accumulated >238-fold in bard1-3 compared with the wild type and were located mainly in the outermost cell layers instead of the usual organizing cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 47 publications
1
69
0
Order By: Relevance
“…A mutation in the BRCA1-associated RING domain1 gene caused both a defect in DNA repair and in the maintenance of SAM organization by repressing WUS expression in plants (Reidt et al, 2006;Han et al, 2008). In a previous study, double-knockdown lines of the cyclin-dependent kinases CDKB2;1 and CDKB2;2 showed abnormal SAMs and phyllotaxis, suggesting a close link between cell cycle progression and the regulation of meristem organization in plants (Andersen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutation in the BRCA1-associated RING domain1 gene caused both a defect in DNA repair and in the maintenance of SAM organization by repressing WUS expression in plants (Reidt et al, 2006;Han et al, 2008). In a previous study, double-knockdown lines of the cyclin-dependent kinases CDKB2;1 and CDKB2;2 showed abnormal SAMs and phyllotaxis, suggesting a close link between cell cycle progression and the regulation of meristem organization in plants (Andersen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…10). It has been suggested that overexpression of WUS and STM may disorganize the SAM (Han et al, 2008) and result in fasciation. Thus, it is likely that DNA damage causes fasciation by promoting the overexpression of WUS and STM.…”
Section: Discussionmentioning
confidence: 99%
“…When low RBR levels persisted, however, meristem activity could not recover and WUS expression was reduced again to normal levels, although CLV3 expression remained low (Figure 3). Thus, WUS expression might be repressed by a CLV-independent mechanism, such as BREAST CANCER ASSOCIATED RING1 (BARD1) (Han et al, 2008), which is strongly upregulated in induced RBRi seedlings (Figure 3). A detailed temporal and spatial analysis of WUS and other genes involved in SAM organization will be required to better understand their functions during RBR downregulation.…”
Section: Rbr Homeostasis Is Critical For Meristem Integrity and Functionmentioning
confidence: 99%
“…Five days after germination on b-estradiol, CYCB1;1 was upregulated in the SAM, as we observed in leaves (see Figure 5). BARD1 (reported to limit WUS expression; Han et al, 2008), is strongly upregulated 5 d after induction. The error bars represent the SE from two biological replicas and two technical replicas.…”
Section: Rbr Regulates Meristemoid Proliferation and Subsequent Stomamentioning
confidence: 99%
“…DPa interacts with the E2Fa transcription factor to form a complex that stimulates the expression of S phase-specific genes, leading to cell division and a delay of cell differentiation (De Veylder et al, 2002). BARD1 has been reported to control SAM organization and maintenance by restricting WUSCHEL (WUS) expression to the organizing center (Han et al, 2008). WUS encodes a homeodomain Figure 6.…”
Section: Ebe-triggered Changes In Gene Expressionmentioning
confidence: 99%